Oxidatively Formed Sugar Radicals in Nucleic Acids - Gimisis, Thanasis; Chatgilialoglu, Chryssostomos (Encyclopedia of Radicals in Chemistry, Biology and Materials, 2012)
Abstract This article focuses on the chemistry of sugar radicals in the context of oxidative damage in nucleic acids. The seven sp3-hybridized CH bonds in 2-deoxyribose (six in ribose) are attacked by reactive oxygen species, generated either by the cell's internal oxygen cycle or by environmental insults, by chemical nucleases including enediyne antibiotics and reactive metal complexes, to generate sugar nucleosidyl radicals. For each position on the 2-deoxyribose or ribose moiety, the factors leading to the generation of the specific sugar radical, together with its fate under aerobic or anaerobic conditions in the nucleoside, nucleotide, single-stranded oligonucleotide, or double helix DNA, are discussed. Furthermore, the model systems that have been constructed for the photochemical-independent generation of each nucleosidyl radical or DNA lesion are described, together with the biochemical studies that have been performed in order to elucidate the stability, reparability, and mutagenic potential of each lesion. Other biologically important events involving modification of nearby nucleobases and the formation of DNA–DNA and DNA–protein cross-links are also discussed.
Keywords: DNA; free radicals; nucleosidyl radical; oxidative damage; sugar radicals